From Scientific Innovation to Popularization of Science: a Theoretical Model TOC ø "1-5" \h \z of Science Communication - Medvedeva, S. M. (Vestnik MGIMO-Universiteta, 2014)
Science communication is process of promotion of scientific ideas from a scientist through scientific community to muss public. Now this research area attracts a lot of attention from scientists. At the same time science communication suffers from the lack of theoretical framework, which can integrate it. In this article we try to contribute to the further theoretical integration of this area. Here we discuss a model of motion and transformation of ideas from the moment of their generation to the time of their appearance in public movies and literature. The model consists of 5 elements: phase of a scientist (generation of ideas); phase of scientific community (promotion of the ideas among scientists); phase of interested groups (communication with business and government, education of future scientists); phase of popular science (promotion of ideas into mass culture); phase of fiction (subject of communication becomes not scientific knowledge, but myth about science). Each phase is conceived as equal in value stage of existence of scientific ideas. There is a consistent interaction between all phases. The ideas can flow sequentially through all five phases. But independent communication among separate stages is also possible. Furthermore, the ideas can flow in both directions from scientific community to public and visa verse. As a result, scientific communication becomes a real dialogue with equal partners.